Automatic knowledge base constructor for Al-Quran retrieval system - Noordin, Mohamad Fauzan; Sharyar, Wani; Tengku, Mohd T. Sembok; Othman, Roslina (The Universal Academy of Science and Technology (UniTech), 2015)
Web 2.0 has changed the strategy of the world. The virtual world has a large impact on the society. There is enormous data on the web but the knowledge behind the data has not been utilized even to the slightest in comparison to its size. Web 3.0 aims at knowledge extraction from the data, there is need to develop means and ways to extract the knowledge behind the data. In this area of research, Muslim researchers have directed their works towards the availability of digital resources for Al- Quran and books of Hadith since they form the foundations of Islam. However, the research done so far has not gone deep into the area of knowledge representation of Al-Quran and Hadith. The current work looks into development of knowledge representation formalism for Al-Quran using the logical base as it is expressive in nature and has proven successful previously even in complex situations. The logical base needs indexing in order for efficient retrieval as well. It would be extremely difficult to maintain the consistency of the logical base if done manually. Hence this work primarly focuses on development of a automatic knowledge base constructor. The current work has a large significance, as it will ease the process of information access to the Muslim community by using the knowledge base for retrieval mechanisms. Not only that the work will be beneficial for Non-Muslims to know more about Al-Quran easily and thus gaining more and more information about Islam.